Rwanda Diagnostic Review of Consumer Protection and Financial Literacy : Private Pensions and Securities, Volume 2. Comparison with Good Practices - World Bank (World Bank, Washington, DC, 2017)
This review of consumer protection and financial literacy (CPFL) in the private pensions and securities sectors in Rwanda complements the 2013 review of Rwanda’s banking, microfinance, and insurance sectors. As noted previously, the institutional elements of the formal financial sector in Rwanda are in place but the levels of financial inclusion are still low. The government pension scheme covers less than 3 percent of the population, and the voluntary private pension funds cover less than 1 percent. The new Pensions Law in Rwanda introduced a comprehensive regulation of the private pension funds, providing a basis for sound consumer protection and opening opportunities for growth, and yet some CPFL issues still need to be addressed. The securities market lists only 7 equities and 9 bonds, capitalized at 27 percent of GDP. The 2011 laws on capital markets regulation introduced a sound regulatory framework that is not yet complete nonetheless and requires stronger investor protection. The key findings and recommendations of the Review – presented in Volume 1 of 2 – detail the main CPFL challenges and the suggested high priority remedies. The full list of recommendations is presented in the annexes. Volume 2 provides a detailed assessment of CPFL in both the private pensions and securities sectors against the international best practices summarized in the World Bank Group’s good practices for financial consumer protection and financial literacy/capability.